2013
DOI: 10.1071/ma13033
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella and egg-related outbreaks

Abstract: ConclusionFood poisoning caused by Cl. perfringens is a preventable condition. If the right checks and balances are built into the food preparation process, then the organism should not have an opportunity to germinate and proliferate. Even if this does occur, thorough reheating of the food at temperatures in excess of 608C will eliminate the organism and prevent an outbreak of food poisoning. This highlights the importance of appropriate education and compliance of personnel involved in food preparation so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Outbreaks of Salmonella infections are associated with consumption of various foods, including poultry, red meats, pork, vegetables, and fruits that can be contaminated with the pathogen. Eggs are the most common single food associated with outbreaks of salmonellosis (CDC, 2006;EFSA, 2009;Jackson et al, 2013;Moffatt and Musto, 2013). A multi-state outbreak of 1939 cases of Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of Salmonella infections are associated with consumption of various foods, including poultry, red meats, pork, vegetables, and fruits that can be contaminated with the pathogen. Eggs are the most common single food associated with outbreaks of salmonellosis (CDC, 2006;EFSA, 2009;Jackson et al, 2013;Moffatt and Musto, 2013). A multi-state outbreak of 1939 cases of Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Both serotypes have the ability to colonize the reproductive organs of hens and are major causes of food borne illness [3]. S. Enteritidis is more commonly linked to contaminated eggs, except in Australia, where the majority of egg-related food borne salmonellosis is caused by S. Typhimurium [14][15][16]. It has been concluded that S. Enteritidis could penetrate the egg shell easier than other serotypes so they supposed that horizontal transmission of Salmonella in eggs is of less importance than the vertical transmission [17].…”
Section: Discussionmentioning
confidence: 99%
“…High proportion of S. Enteritidis in egg-related outbreaks may be due to the capacity of the pathogen for trans-ovarian transmission (Moffatt and Musto, 2013). However, it is not clear whether vertical or horizontal contamination is more important in S. Enteritidis infection (Messens et al, 2005;Moffatt and Musto, 2013). For other serotypes of Salmonella enterica, fecal contamination of eggshell is considered as the most likely source of the pathogen (Cantor and McFarlane, 1948;Huchison et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…For examples, S. Enteritidis and S. Heidelberg were responsible for 83% and 9%, respectively, of egg-related outbreaks of salmonellosis occurred in the US (Jackson et al, 2013). High proportion of S. Enteritidis in egg-related outbreaks may be due to the capacity of the pathogen for trans-ovarian transmission (Moffatt and Musto, 2013). However, it is not clear whether vertical or horizontal contamination is more important in S. Enteritidis infection (Messens et al, 2005;Moffatt and Musto, 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation